2016
DOI: 10.1177/1747954116644063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the intention to hit a disguised backhand drop shot on skilled tennis performance

Abstract: The purpose of this study was to examine the effect of the intention to hit a disguised backhand drop shot on tennis performance. Skilled tennis players (n ¼ 10) were videotaped while hitting drop shots with and without instruction to disguise the shot. Results calculated via three-dimensional motion analysis indicated that disguised drop shots involved more shoulder rotation and greater transition movement forward than control condition drop shots. To disguise drop shots, tennis players used exaggerated shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“… Smeeton and Williams (2012) analyzed the kinematics of penalty kicks and found significant differences between non-deceptive and deceptive kicks at multiple markers spanning both the upper and lower body and across all occlusion points. Iwatsuki et al (2016) reported similar results when they compared normal tennis backhand drop shots or when they gave the impression of setting up a backhand slice. Kinematic analysis revealed that the center of mass (COM) moved more forward, horizontal shoulder rotation and twist angle were greater, and racket surface area was higher on tricky drops than on unmasked drop shots.…”
Section: Introductionmentioning
confidence: 69%
“… Smeeton and Williams (2012) analyzed the kinematics of penalty kicks and found significant differences between non-deceptive and deceptive kicks at multiple markers spanning both the upper and lower body and across all occlusion points. Iwatsuki et al (2016) reported similar results when they compared normal tennis backhand drop shots or when they gave the impression of setting up a backhand slice. Kinematic analysis revealed that the center of mass (COM) moved more forward, horizontal shoulder rotation and twist angle were greater, and racket surface area was higher on tricky drops than on unmasked drop shots.…”
Section: Introductionmentioning
confidence: 69%